Parental monitoring, adolescent dishonesty and underage drinking: A nationally representative study - Lushin, Viktor; Jaccard, James; Kaploun, Victor (Journal of adolescence (London, England.), 2017)
Little research has connected underage drinking with adolescent information management strategies. The present study uses longitudinal analyses to theoretically link adolescent lying with parental “monitoring knowledge,” and, in turn, with prospective adolescent drinking, in a large nationally representative sample of U.S. seventh- and eighth-graders (N = 4020). Structural equation modeling evaluated and supported, two key hypotheses: (1) dishonesty promotes future alcohol use by decreasing parental monitoring knowledge, and (2) dishonesty directly predicts alcohol consumption independent of its effects on parental monitoring. Maternal warmth and adolescent satisfaction with maternal relationships, but not parental control, were associated with lessened lying, and predicted parental monitoring and underage drinking. Our data implicate the role of adolescent agency for parental monitoring and highlight advantages of cohesive as opposed to over-restrictive parenting.